Predicting Earnings Manipulation Using Beneish M - Score of Selected Companies in India - Shah, Charmi; Saraswat, Mehul; Mehta, Akshay (Indian Journal of Finance, 2018)
In the field of global competition, the corporate world is witnessing manipulation of financial statements to achieve the desired outcomes. According to India Forensic Consultancy Services, at least 1200 companies listed on domestic stock exchanges counterfeited their financial statements. The increasing rate of such undesired acts laid path for the investigation into such practices. This empirical research work was conducted to predict the signs of earnings manipulation of companies listed with the BSE 100 index by using the probabilistic Beneish M score eight variable model. Time frame for the investigation of financial statements' data was confined to 2011 to 2016 to calculate the M score. Based on M score results of each year, the companies were classified into two groups: likely manipulator and non-likely manipulator. Then multinomial regression technique was used to find the most significant variables that affected manipulation. The outcomes of the results revealed that three ratios, namely TATA (total accruals to total assets), DSRI (daily sales in receivables index), and SGI (sales growth index) variables could be considered as signals of earnings manipulation by companies. The present work contributes to the literature through identification of probable earnings manipulators in BSE 100 index companies which investors prefer the most for their equity investments. The research findings may be an eye-opener for regulators /policy makers to implement stringent checks on auditing of financial results of the companies. Furthermore, the research would be useful for the investors to go for face validation of companies instead of relying on misrepresentation of their true value.